SOU: tênis personalizado e customizável através das tecnologias de prototipagem rápida - Kick, Paulo Guilherme Simão [UNESP] (2017)
The proposal of this project is the study and creation of a customizable footwear through the processes of Additive Manufacture and Rapid Prototyping. These concepts (AM) and (RP) develop into tecnologies that generate a 3D product created directly from a CAD program. These processes of production are based on addition, conformation or subtraction of materials. Additive Manufacture (popularly known as 3D impression), offers a range of advantages comparing to traditional manufacture methods, such as utilization of complex geometrical structures, use of alternative materials and development of products that can be easily customizable and ready to be produced in different sizes, colors, settings, etc.